Pink Dominance and ‘Semua Karena Cinta’ Symbolism in Government City Branding Communication - Roudhotun, Cinta Manda; Pia Wulandari, Maulina; Muwafik Saleh, Akhmad (Graduate School, Universitas Brawijaya, 2026)
Abstract This study explores how a government-led city branding initiative can become a site of public contestation when symbolic meanings are not collectively negotiated. In 2025, the Jember Regency Government introduced the slogan “Semua Karena Cinta” (All Because of Love) and a pink-dominated visual identity as part of its official branding strategy. Using a qualitative case study approach grounded in a constructivist perspective, this research examines how the branding was interpreted, debated, and resisted in public communication spaces. Data were gathered from official government publications and Instagram content, online news coverage, social media comments, and in-depth interviews with community members, and analyzed through thematic coding with NVivo. The findings show that public resistance was driven by perceived misalignment between the pink symbolism and Jember’s socio-cultural identity, the saturation of visual symbols in public facilities, and a gap between the “love” narrative and visible political dynamics. Rather than outright policy rejection, resistance appeared mainly through humor, sarcasm, and critical digital discourse, indicating tensions in symbolic legitimacy. Theoretically, this study contributes to city branding scholarship by applying Issue Management Theory to interpret public resistance as an early signal of meaning misalignment. Practically, it highlights the importance of participatory and dialogic communication in sustaining trust and legitimacy in government branding initiatives.